Factors affecting bird communities in fragments of secondary pine forests in the north-western Mediterranean basin - Brotons, L; Herrando, S (ACTA OECOLOGICA-INTERNATIONAL JOURNAL OF ECOLOGY, 2001)
We assessed the influence of size, extent of isolation and vegetation structure of secondary forest fragments on the richness and species composition of breeding bird communities in a sample of pine forest fragments surrounded by an agricultural matrix in the north-western Mediterranean basin. Fragment size was the main predictor of bird's occurrence, since it accounted for 70 % of the model variation. Isolation was also a valuable predictor of species occurrence, especially for forest specialists. Finally, subarboreal vegetation such as holm oak and a well-developed tree layer of large pines favoured forest species occurrence. Therefore, in spite of the long history of human impact, forest birds in Mediterranean mosaics are sensitive to both habitat loss and isolation of remnant patches in a similar manner to the patterns found in other temperate fragmented landscapes where human impact is more recent. (C) 2001 Editions scientifiques et medicales Elsevier SAS.
Keywords: birds; fragmentation; isolation; Mediterranean mosaics; vegetation structure